Analisis Diskriminan Perilaku Pengambilan Keputusan Ibu-Ibu Rumah Tangga pada Ritel Modern Hypermart di Pontianak - Heng, Lie (MABIS, 2011)
This research is conducted to find out factors influencing the decision making by the housewives and also to findout whether there are differences in factors influencing the decision making of the groups of housewives who are frequently or seldom to buy products at Hypermart modern retailer in Pontianak. The data is collected through questionaire that is arranged in likert scale and given to 300 respondents who are the consumers of Hypermarket in Pontianak by using purposive sampling technique. The data is then analyzed by using factor analysis technique and discriminant analysis. The result of this research shows that the factors determining the decision making are price, quality, recreational, choices, and the trend. The result of discriminant analysis shows that there are differences in factors determining the decision making in buying between the group that is frequently and the group that is seldom or not frequently in buying products of Hypermart. The defference is caused by the influence of quality and the trend.